Agmatine ameliorates diabetes type 2-induced nephropathy in rats - Fatemah O Kamel; Ohoud Shagroud; Mai A.Alim A.Sattar Ahmad; Gamal S Abd El-Aziz; Abdulhadi S Burzangi; Duaa Bakhshwin; Maha Jamal; Shahid Karim (Asian Pacific Journal of Tropical Biomedicine, 2024)
Objective: To assess the nephroprotective potential of agmatine in a rat model of streptozotocin-induced diabetic nephropathy. Methods: A single dose of streptozotocin (40 mg/kg) coupled with a fructose diet induced diabetes in Wistar rats. Agmatine (40 and 80 mg/kg) was administered to rats for 12 weeks. The body weight and fasting blood glucose were measured weekly. Insulin level, urine output, total protein, albumin, blood urea nitrogen, creatinine, and cystatin-C were also determined at the end of the experiment. Furthermore, superoxide dismutase, glutathione, interleukin-1β, interleukin-6, and tumor necrosis factor-alpha were evaluated in kidney tissue. Histopathological study was also performed using hematoxylin and eosin staining. Results: Agmatine at both doses significantly increased final body weight, and lowered fasting blood glucose, urine output, insulin, total protein, albumin, blood urea nitrogen, creatinine, and cystatin-C levels compared with the diabetic group (P < 0.05). Inflammatory markers and antioxidant effect were significantly improved in agmatine-treated rats. Moreover, the histopathological changes in renal structure were ameliorated by agmatine treatment. Conclusions: Agmatine alleviates diabetic nephropathy by improving renal functions and reducing inflammation and oxidative stress. The molecular mechanisms of its nephroprotective actions need to be investigated in future study.